2023
DOI: 10.1088/1367-2630/acd26e
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of adaptive reward and reinforcement learning rules on cooperation

Abstract: Understanding cooperative behavior in multi-agent system is a research hotspot. In the context of pairwise interaction games, several researches have used reinforcement learning rules to successfully explain and predict the behavior of agents. However, multi-agent interactions are more general than two-agent interactions, and the effect of reward mechanism on behavior of agents is also ignored under the reinforcement learning rules. Therefore, this paper established a framework that combines the public goods g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Moreover, in contrast to existing works that combine RL with game theory [55,59,70], our model incorporate more environmental information (neighbors' decisions) to expand the state space, which enables individuals to more effectively tailor their responses to diverse environments, ultimately enhancing the overall performance of the population. It may provide a relatively simple explanation for the emergence of cooperation under this introspective learning mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in contrast to existing works that combine RL with game theory [55,59,70], our model incorporate more environmental information (neighbors' decisions) to expand the state space, which enables individuals to more effectively tailor their responses to diverse environments, ultimately enhancing the overall performance of the population. It may provide a relatively simple explanation for the emergence of cooperation under this introspective learning mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [56,57] explored the emergence of cooperation characterized by explosiveness and cyclic oscillations in two-player games, and found that the herding effect could be effectively eliminated in minority games [58]. Furthermore, the incorporation of other mechanisms, such as adaptive reward [59], social payoff [55], extortion strategy [60], and Lévy noise [61], has shown to significantly improve the level of cooperation. Nonetheless, the self-regarding Q-learning approach, which emphasizes policy updates based on one's experience, leads to an alignment of individual state space with strategy space, thereby overlooking environmental cues.…”
Section: Introductionmentioning
confidence: 99%